Creative Movement and Anti-Gentrification: Learning from Los Tjihapit Market's Coffee in Bandung - Hajaria, Nirmala; Nabila, Adha Ika Putri; Puteri, Lidhiya Ananda Rizki; Syarifah, Maryam Shofi; Ekomadyo, Agus Suharjono (CV. Gio Architect, 2024)
The phenomenon of gentrification, driven by the presence of the creative class, is a consequence of the global implementation of the Creative City concept. Bandung has adopted this concept, and one of the areas developed by the creative class is the Cihapit Market area. This article examines how the